Transformasi Digital dalam Pengelolaan Sumber Daya Air dan Smart Tourism untuk Keberlanjutan Ekowisata di Lumbang Kabupaten Probolinggo - Rofiuddin, Mohammad; Robi’in, M. (MODELING: Jurnal Program Studi PGMI, 2025)
The management of water resources and the promotion of nature-based tourism in Desa Lumbang, Kabupaten Probolinggo still face various challenges, particularly in the utilization of digital technology. Digital transformation has the potential to enhance the efficiency of water resource management and strengthen tourism marketing strategies. However, its implementation remains limited due to inadequate infrastructure, low digital literacy, and insufficient funding. This study employs a qualitative approach using a case study method, where data is collected through in-depth interviews, observations, and document analysis. The data is then analyzed using thematic analysis and SWOT analysis, and validated through source and method triangulation. The findings indicate that water resource management still relies on conventional administrative recording and manual water flow monitoring, while Internet of Things (IoT) technology has not yet been implemented. In the tourism marketing aspect, the utilization of SEO, interactive social media, and influencer-based campaigns remains suboptimal, limiting the destination's exposure. To enhance management effectiveness and attract more visitors, a smart tourism-based strategy is needed, including the use of QR Codes for tourism education, content-based marketing, and online booking platforms. Increasing digital literacy among the community and establishing partnerships with external stakeholders are strategic steps to ensure the sustainability of this program. Abstrak Pengelolaan sumber daya air dan promosi wisata berbasis sumber daya alam di Desa Lumbang, Kabupaten Probolinggo masih menghadapi berbagai tantangan, terutama dalam pemanfaatan teknologi digital. Transformasi digital berpotensi meningkatkan efisiensi pengelolaan sumber daya air serta memperkuat strategi pemasaran wisata, namun penerapannya masih terbatas akibat minimnya infrastruktur, rendahnya literasi digital, serta kurangnya pendanaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, di mana data dikumpulkan melalui wawancara mendalam, observasi, dan analisis dokumen, kemudian dianalisis menggunakan analisis tematik dan SWOT, serta divalidasi dengan triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa pengelolaan sumber daya air masih bergantung pada pencatatan administratif konvensional dan pemantauan debit air manual, sementara teknologi Internet of Things (IoT) belum diterapkan. Dalam aspek pemasaran wisata, pemanfaatan SEO, media sosial interaktif, dan kampanye berbasis influencer masih belum optimal, sehingga eksposur destinasi wisata terbatas. Untuk meningkatkan efektivitas pengelolaan dan daya tarik wisata, diperlukan strategi berbasis smart tourism, seperti QR Code untuk edukasi wisata, pemasaran berbasis konten visual, serta platform pemesanan online. Peningkatan literasi digital masyarakat dan kemitraan dengan pihak eksternal menjadi langkah strategis dalam mendukung keberlanjutan program ini.